Impact of anesthesia method on cortisol and interleukin-6 concentration changes during and after laparoscopic colorectal surgery - Gasiūnaitė, Diana; Šipylaitė, Jūratė; Kontrimavičiūtė, Eglė; Poškus, Eligijus (Acta medica Lituanica, 2012)
Results and discussion. There were statistically significant differences be tween the groups in pain score after surgery (p